The Concept of Al-Milkiyyah in Islam: A Study of Ownership Rights in the Muamalah System - Yadrizal Yadrizal; Wahyu Ramadhani; Adiman Adiman; Aidil Alfin (Al-Afkar: Jurnal Pemikiran dan Pendidikan Islam, 2026)
This article provides a profound and comprehensive analysis of the construction of the concept of al-milkiyyah (property rights) from an Islamic perspective, as well as its dynamic application within the contemporary muamalah system. As a solution-oriented alternative to the failures of capitalist and socialist economic systems, Islamic economics offers a highly unique concept of ownership. This philosophical-legal framework is fully grounded in the core theological principle that Allah SWT is the absolute and ultimate owner of everything in the universe, while humans merely act as trustees ( istikhlaf ) who bear a huge responsibility as caliphs on earth. (b) specifically, this study aims to radically examine the three-dimensional division of ownership, which encompasses private ownership, public ownership, and state ownership. Furthermore, this research delineates the legitimate causes of ownership ( asbab al-tamalluk ), while attempting to reconstruct Islamic law in response to the current dynamics of disruption and digitalization in the global economy. (c) Utilizing a descriptive qualitative research method based on library research, the data analysis process was carried out descriptively-analytically as well as comparatively across classical jurisprudence ( fiqh ) schools of thought and contemporary scholars' ideas. (d) The results of the study explicitly demonstrate that despite a massive shift from physical possession ( qabdh haqiqi ) toward virtual legal/digital possession ( qabdh hukmi ), the concept of al-milkiyyah proves to remain adaptive, elastic, and relevant in protecting individual private rights while simultaneously safeguarding the public interest ( hifzh al-mal ). As a final recommendation, aligning religious texts with the disruptive digital context requires a strict strengthening of the Shariah Governance Framework to minimize social inequality and economic exploitation.